Exploration of identifying individual tumor tissue based on probabilistic model - Hu, Yuhan; Zhu, Qiang; Dai, Xuan; Zhang, Mengni; Chen, Nanxiao; Wang, Haoyu; Wang, Yuting; Cao, Yueyan; Wang, Yufang; Zhang, Ji (Frontiers in Oncology, 2024)
Variations in the tumor genome can result in allelic changes compared to the reference profile of its homogenous body source on genetic markers. This brings a challenge to source identification of tumor samples, such as clinically collected pathological paraffin-embedded tissue and sections. In this study, a probabilistic model was developed for calculating likelihood ratio (𝐿𝑅) to tackle this issue, which utilizing short tandem repeat (STR) genotyping data. The core of the model is to consider tumor tissue as a mixture of normal and tumor cells, and to introduce the incidence of STR variants (φ) and the percentage of normal cells (𝑀 𝑥𝑛 ) as priori parameters when performing calculations. The relationship between 𝐿𝑅 values and φ or 𝑀 𝑥𝑛 was also investigated. Analysis of tumor samples and reference blood samples from 17 colorectal cancer patients showed that all samples had 𝐿𝑜𝑔 10 (𝐿𝑅) values greater than 10 14 . In the non-contributor test, 99.9% of the quartiles had 𝐿𝑜𝑔 10 (𝐿𝑅) values less than 0. When the defense's hypothesis took into account the possibility that the tumor samples came from the patient's relatives, 𝐿𝑅 greater than 0 were still obtained. Furthermore, this study revealed that 𝐿𝑅 values increased with decreasing φ and increasing 𝑀 𝑥𝑛 . Finally, 𝐿𝑅 interval value was provided for each tumor sample by considering the confidence interval of 𝑀 𝑥𝑛 . The probabilistic model proposed in this paper could deal with the possibility of tumor allele variability and offer an evaluation of the strength of evidence for determining tumor origin in clinical practice and forensic identification.